2018
DOI: 10.2478/hukin-2018-0043
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Muscle Stiffness of the Trapezius Muscle after Application of Ischemic Compression into Myofascial Trigger Points in Professional Basketball Players

Abstract: The study aimed to assess the effects of compression trigger point therapy on the stiffness of the trapezius muscle in professional basketball players (Part A), and the reliability of the MyotonPRO device in clinical evaluation of athletes (Part B). Twelve professional basketball players participated in Part A of the study (mean age: 19.8 ± 2.4 years, body height 197 ± 8.2 cm, body mass: 91.8 ± 11.8 kg), with unilateral neck or shoulder pain at the dominant side. Part B tested twelve right-handed male athletes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
67
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(78 citation statements)
references
References 38 publications
(34 reference statements)
4
67
1
Order By: Relevance
“…Due to the excessive use of the trapezius muscles, shoulder joint instability may occur due to relative muscle weakness or imbalance of the activation pattern between the muscles, and secondary impingement syndrome may appear [26]. It has been reported that if the shoulder range of motion is improved by reducing the tension of the UT muscles, the risk of injury to athletes can be reduced [21]. The IS muscle is the involved rotator cuff muscle of the shoulder joint.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the excessive use of the trapezius muscles, shoulder joint instability may occur due to relative muscle weakness or imbalance of the activation pattern between the muscles, and secondary impingement syndrome may appear [26]. It has been reported that if the shoulder range of motion is improved by reducing the tension of the UT muscles, the risk of injury to athletes can be reduced [21]. The IS muscle is the involved rotator cuff muscle of the shoulder joint.…”
Section: Discussionmentioning
confidence: 99%
“…Among the muscle tension of the shoulders, the examination was performed on the UT and IS muscles, which are correlated with the inward and backward rotations and the inner and outer rotations. In order to assess the muscle tone, UT was marked with a surgical marker pen in the middle part of the line connecting the spinous process of C7 and the end of the acromion, and the middle belly of the infraspinatus fossa for IS [21]. Subjects sat on a chair with a backrest to relax and maintain a comfortable posture.…”
Section: Muscle Tonementioning
confidence: 99%
“…Current guidelines for the treatment of LBP endorse physical exercise programs and a range of other non-pharmacological complementary therapies including manual therapy, acupuncture, spinal manipulation and yoga [15]. Myofascial trigger points (MTrPs) compression therapy is a well-studied form of non-pharmacological complementary manual therapy, which aims to induce temporary local ischemia and over-stimulation of mechanoreceptors in order to restore tissue normal functional conditions and healing response [7][8][9].…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that continuous compression at MTrPs over-stimulates local mechanoreceptors which leads to neurotransmitters depletion and results in pain attenuation. Also, rapid reperfusion with oxygenated blood, ones the obstruction of the local blood ow is released, is believed to restore the normal functional conditions of the muscle and contribute to its recovery [7][8][9]. Several studies evaluated the effect of MTrPs compression therapy on musculoskeletal pain syndromes and found it to be effective in relieving pain and disability [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, reduced hydration of FTs reduces their elasticity, leading to a kind of gluing (tissue adhesion) and the formation of painful trigger points (Behm and Wilke, 2019). Trigger points may affect the formation of musculoskeletal and fascial imbalance, which is biomechanically related to the persistence of abnormal posture and motor dysfunction (Kisilewicz et al, 2018;Wilke et al, 2018a;Behm and Wilke, 2019).…”
Section: Introductionmentioning
confidence: 99%